A rare case of Epstein‐Barr virus‐associated hepatosplenic smooth muscle tumors after kidney transplantation. Issue 3 (3rd March 2018) - Pircher, C.; Schneeberger, S.; Boesmueller, C.; Agaimy, A.; Zoller, H.; Bale, R.; Henninger, B.; Mayer, G.; Neuwirt, H.
Abstract: A 27‐year old caucasian male was diagnosed 2.7 years after kidney transplantation with Epstein‐Barr virus (EBV)‐associated smooth muscle tumors in liver and spleen. The reduction in immunosuppression and conversion from tacrolimus to sirolimus did not lead to a regression of the tumors. Additionally, the patient developed a cellular rejection of his renal allograft, which was successfully treated. A combined approach with stereotactic radiofrequency ablation (SRFA) and surgical resection was effective in the treatment of the tumors.